2011
DOI: 10.1080/08870446.2010.525640
|View full text |Cite
|
Sign up to set email alerts
|

Communicating BRCA1/2 genetic test results within the family: A qualitative analysis

Abstract: Genetic testing for BRCA1/2 mutations associated with hereditary breast and ovarian cancer reveals significant risk information about one's chances of developing cancer. It is important to study communication processes in families where members are undergoing genetic testing because the information received is crucial not just to the individual concerned but also to other members of the biological family. This study investigates family communication of BRCA1/2 test results from both the informants' and recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
5
42
0
1
Order By: Relevance
“…These differences may have contributed to the lower level of accuracy among relatives. As previous research has suggested, there are a number of possible reasons why information may not be recalled following genetic counselling about a BRCA1/2 mutation, including lack of understanding, 24 individual interpretation or perceived lack of relevance 8 and not valuing the information sufficiently to retain it. 11 A lower level of accuracy was seen for hereditary cancer than for genetics among patients and relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may have contributed to the lower level of accuracy among relatives. As previous research has suggested, there are a number of possible reasons why information may not be recalled following genetic counselling about a BRCA1/2 mutation, including lack of understanding, 24 individual interpretation or perceived lack of relevance 8 and not valuing the information sufficiently to retain it. 11 A lower level of accuracy was seen for hereditary cancer than for genetics among patients and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…5 Families prefer information to be passed on by the patient; 6 yet, although most families do appear to communicate genetic information, 5 patients do not always share all information with all at-risk relatives. 7,8 There are many barriers to family communication about hereditary cancer, 9 including lack of a close relationship, 6 reluctance to upset relatives, 10 youth or emotional readiness of relatives, 11 family culture, 8 perception of the risks and benefits of the information 12 and personal beliefs about the causes of genetic illness. 13 Information about a cancer-predisposing gene mutation does not necessarily lead to changes in risk perception, 1 although the way in which information is communicated within families may influence the uptake of genetic counselling and screening.…”
Section: Introductionmentioning
confidence: 99%
“…Where consequences seemed more controllable and not necessarily fatal, the obligation was thought to be weaker. For instance, Dancyger et al (2011) reported that information was edited or withheld in HBOC families if those who were tested considered the recipient's capacity to cope with the information as diminished.…”
Section: Disclosure (B2)mentioning
confidence: 99%
“…Genetic counselors encourage counselees to inform at-risk relatives about their genetic test result and the availability of surveillance measures [4]. This holds in particular for the first person within a family who attends genetic counseling: 'the index patient'.…”
Section: Introductionmentioning
confidence: 99%
“…This holds in particular for the first person within a family who attends genetic counseling: 'the index patient'. Index patients are central in sharing information and facilitating informed decision-making concerning risk management options for relatives [4].…”
Section: Introductionmentioning
confidence: 99%